(untitled) (Research, Society and Development, 2021)
• Coli ATCC 25922 inactivation was studied to determine the effect of high-pressure carbon dioxide (HPCD) process on pumpkin puree. Experiments were performed using a batch HPCD system at three conditions of pressure (7.5 MPa, 17.5 MPa and 27.5 MPa) at 32 °C. Afterwards, at the best experimental condition (27.5 MPa – 275 bar), a kinetic was performed to assess inactivation of microorganisms over time (from 1 to 8 h). The physicochemical characteristics (pH, total soluble solids – TSS, titratable acidity – TA, total carotenoids, total reducing sugars – TRS, moisture and optical microscopy) of the pumpkin puree were also evaluated. HPCD with acidification increases bacterial efficacy of treatments, as well as significant changes in physicochemical parameters. HPCD treatment reduced the microbial load moderately in all experiments, by a maximum of approximately 3.17 log cycles in 8 h of process at 27.5 MPa (275 bar). Optical microscopy showed no difference in cell wall, just in starch which was expected by cooking.